Caracterização da proteína de fusão ZZ-AmyLuc e sua otimização para imunoensaios - Cavalcante, Maysa de Souza (Universidade Federal de São Carlos, 2024)
Immunoassays are widely used in biomedical analysis based on antigen-antibody interaction, in which they are capable of detecting antibodies against specific antigens. In general, the most sensitive commercial assays mainly use chemiluminescence as a detection method. However, current chemiluminescence methods based on the enzyme horseradish peroxidase (HRP) conjugated with secondary antibody and luminol show a rapid decay of luminescence. Thus, the new fusion protein, ZZ-AmyLuc, built from the luciferase of the firefly Amydetes vivianii fused to the ZZ portion of protein A (VIVIANI et al., 2021), proved to be a good alternative. This protein has a stronger blue-green glow, with greater bioluminescent activity, in addition to being very thermostable and presenting more sustained emission, capable of lasting several minutes (t1/2 > 30 min). Furthermore, it was notably capable of detecting type G immunoglobulins (IgG), including the anti-nucleoprotein of the SARS-CoV-2 virus and its respective antigen. The detection could be observed using photodetection cameras (CCD) and even common smartphone cameras, supporting its high efficiency in both immunoassays and Western Blotting techniques. However, a more detailed physicochemical characterization of ZZ-AmyLuc had not yet been carried out, requiring its in vitro stabilization and optimization of the sensitivity of the detection assay for use in bioluminescent immunoassays, particularly for the detection of the SARS-CoV-2 nucleoprotein. For that, the kinetic properties were determined, namely the KMs for ATP and D-luciferin, the optimal pH for bioluminescent activity and IgG binding, thermostability at 4 ºC, -20 ºC and 37 ºC, as well as the optimization of the sensitivity of photometric detection assay in immunoassays.
Characterization of the ZZ-AmyLuc fusion protein and its optimization for immunoassays
Keywords: Amydetes vivianii; Bioluminescência; Domínio ZZ; Luciferase; Bioluminescence; ZZ-domain; CIENCIAS BIOLOGICAS::BIOQUIMICA::BIOLOGIA MOLECULAR